Development and psychometric evaluation of a psychosocial quality-of-life questionnaire for individuals with autism and related developmental disorders. (October 2016) - Markowitz, Leslie A; Reyes, Charina; Embacher, Rebecca A; Speer, Leslie L; Roizen, Nancy; Frazier, Thomas W
This study investigated the psychometric properties of the Child and Family Quality of Life scale, a measure of psychosocial quality of life in those with autism and related developmental disorders. Parents of 212 children suspected of autism spectrum disorder completed the Child and Family Quality of Life prior to a diagnostic evaluation. Results indicated that the Child and Family Quality of Life measured six unique quality-of-life constructs (child, family/caregiver, financial, external support, partner relationship, and coping), had good reliability across score ranges and exhibited expected patterns of convergent validity. Caregivers of autism spectrum disorder–affected children reported reduced family quality of life prior to the time of diagnosis relative to caregivers of children with other developmental disabilities. The Child and Family Quality of Life is a brief, reliable measure for assessing psychosocial quality of life in families affected by developmental disability. This study is the first to demonstrate impairments in family quality of life early in the developmental course of autism spectrum disorder, prior to formal diagnosis. In addition to traditional child-focused intervention strategies, families with autism spectrum disorder–affected children require early, broad intervention strategies that positively impact the whole family.